1987
DOI: 10.1093/oxfordjournals.aje.a114716
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Food Frequency Methods of Measuring Dietary Calcium Intake

Abstract: To assess the ability of food frequency methods to measure current dietary calcium intake in elderly women, the authors administered two types of food frequency instruments to 37 randomly selected women who attended two senior citizens centers in San Francisco, and they compared those responses to seven-day food records. A 34-item food frequency instrument (with portion sizes rated as small, medium, or large) correlated well (r = 0.76) with the estimated calcium intake from seven-day records. Limiting the inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
128
0
2

Year Published

1991
1991
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(134 citation statements)
references
References 0 publications
4
128
0
2
Order By: Relevance
“…Block and Hartman (1989) have pointed out that age appears to have little adverse affect on the validity of questionnaires, at least when administered by interview, which is in concordance with the impression in this study. Different authors have found a good correlation to reference data among older respondents (Cummings et al, 1987;Sobell et al 1989;Brown, Fisher and Johnson, 1993), and better response rates among elderly than younger subjects have also been found (Jørgensen et al, 1993). A tendency to over reporting of 'desirable' food items such as fruit, bread and potatoes has been reported (Pietinen et al, 1988;Nes et al, 1992).…”
Section: Design and Quality Of The Dietary Assessment Instrumentmentioning
confidence: 89%
“…Block and Hartman (1989) have pointed out that age appears to have little adverse affect on the validity of questionnaires, at least when administered by interview, which is in concordance with the impression in this study. Different authors have found a good correlation to reference data among older respondents (Cummings et al, 1987;Sobell et al 1989;Brown, Fisher and Johnson, 1993), and better response rates among elderly than younger subjects have also been found (Jørgensen et al, 1993). A tendency to over reporting of 'desirable' food items such as fruit, bread and potatoes has been reported (Pietinen et al, 1988;Nes et al, 1992).…”
Section: Design and Quality Of The Dietary Assessment Instrumentmentioning
confidence: 89%
“…Dietary intake of Ca and protein were estimated by questionnaires. 40 Women were weighed (Scaletronix, White Plains, NY, USA) and height measured with a stadiometer (Perspective Enterprises, Portage, MI, USA) at each visit associated with a DEXA study. Blood pressure was measured with an automatic sphygmomanometer (DinaMap, GE Healthcare/GE Medical Systems Inc., USA) and measured in the same arm at each visit after the patient was settled and before venipuncture was performed.…”
Section: Californiamentioning
confidence: 99%
“…Total score, correlation analysis (not defined): (18) Tools to measure calcium and/or dairy intake in adults and reported moderate κ values for both dairy foods and Ca (0·60-0·76) (27) . However, results of the Bland-Altman analysis conducted in the same study indicated only 52 % exact agreement and very wide limits of agreement (±1000 mg) indicating that this tool would not perform well at the individual level (27) .…”
Section: -3 Weeksmentioning
confidence: 99%